Interet D’une Supplementation En Spiruline Chez Les Enfants Drepanocytaires Homozygotes A L’hopital National De Niamey. (Essai Clinique Randomise En Double Aveugle A Propos De 53 Cas) - B., Malam-Abdou; S., Brah; A., Andia; Sani MA, Mahamane; M., Chefou; F., Ibrahim; H., Diongolé; A., Harissou; I., Daouda; D., Alhousseini Maïga; S., Mahamadou (European Scientific Journal, ESJ, 2017)
Spirulina is a micro algae used for thousands of years due to its healing properties. We supplemented children suffering from sickle cell anemia in order to appreciate its impact on the anthropometrical and clinical parameters. It consisted of a randomized clinical double blind test which was carried during a period of 9 months. The study concerned 53 homozygotes children suffering from sickle cell anemia aged 6 months to 15 years. Also, they were visiting the National Hospital of Niamey for follow up. One group (28 children) received 5 g of spirulina daily, and the other group (25 children) received placebo. The aspects studied were: the number of hospitalizations and transfusions, the vaso-occlusive crisis, the body mass index, and the splenomegalia. We found that 84.90% of patients were hospitalized at least once and 45.3% of them have already been transfused. The average number of crisis has greatly decreased in the spirulina group from 2.75 before the study to 1.18 at the end of the study. This, thus, was observed when compared to 2.44 to 1.6 in the placebo group. We also noticed a decrease of the number of hospitalizations and the number of transfusions which is less important in the group supplemented with spirulina. In conclusion, this study showed that supplementation in spirulina had a significant impact on children suffering from sickle cell anemia. This is even despite the fact that the difference between the two groups is not significant in some cases.